Spatio-temporal differentiation of landslide after the Ms6.5 Ludian earthquake in Yunnan Province - Rufen ZI; Jiajia LIU; Yuhong WANG; Ping DUAN; Jia LI (Zhongguo dizhi zaihai yu fangzhi xuebao)
A large number of landslides were triggered by the Ms6.5 magnitude earthquake that occurred in Ludian, Yunnan Province, on August 3, 2014. Landslides triggered by strong earthquakes exhibit slow post-earthquake recovery, high recovery difficulty, and tend to recur and expand, which can have long-term impacts on roads, water bodies, and ecological environments. Therefore, it is necessary to explore their long-time spatial and temporal variability. Taking the 314 km2 area affected by the earthquake as the study area, post-earthquake landslides were first extracted and a multi-temporal data list was compiled using the ENVI deep learning method. Based on this, the spatial-temporal differentiation analysis was carried out focusing on the spatio-temporal distribution characteristics of landslides, changes in spatio-temporal area, and the evolution of landslide activities. The results show that: (1) following the earthquake, the number and area of landslides increased dramatically, gradually decreasing over the subsequent 8 years. Earthquake-triggered landslides were primarily small-scale, with an area of less than 0.01 km2, concentrated on both sides of the river valley, and distributed more prominently within 2 000 meters from the epicenter and within seismic intensity Ⅸ; (2) over time, the post-earthquake landslide activity rate generally showed a gradual weakening trend, with only 6.08% of the earthquake-triggered landslides still active as of July 2022, indicating a gradual weakening of the earthquake's impact on landslides; (3) the activity evolution of post-earthquake landslides can be divided into three phases: the period of strong landslide activity (August 2014-July 2016), the period of moderate activity (August 2016-August 2021), and the period of weak activity (September 2021-July 2022).